FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL DAN MENENGAH DI KABUPATEN PATI - Nabillah Mahardika Aristawati Sutanto; Meiriska Febrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research aims to examine the factors that have an influence on tax compliance. The independent variables used in this study are tax knowledge variables, tax sanctions, tax modernization, tax services, reduction in final income tax rates, socialization of incentives for PMK 86/2020 on the dependent variable of taxpayer compliance. The population of this study is all registered micro, small and medium enterprises in Pati Regency. study uses the convenience sampling method with 61 respondents who are taxpayers of micro, small and medium enterprises as the research sample. Multiple regression model was used to analyze the data. The results of this study indicate that tax knowledge affects taxpayer compliance while tax sanctions, tax modernization, tax services, lowering final income tax rates and socialization of tax incentives PMK 86/2020 have no effect on taxpayer compliance of micro, small and medium enterprises in Pati Regency.